Biomimetic collagen biomaterial induces in situ lung regeneration by forming functional alveolar. (April 2020) - Wang, Linjie; Zhao, Yannan; Yang, Feng; Feng, Meng; Zhao, Yazhen; Chen, Xi; Mi, Junwei; Yao, Yuanjiang; Guan, Dongwei; Xiao, Zhifeng; Chen, Bing; Dai, Jianwu
Abstract: In situ restoration of severely damaged lung remains difficult due to its limited regeneration capacity after injury. Artificial lung scaffolds are emerging as potential substitutes, but it is still a challenge to reconstruct lung regeneration microenvironment in scaffold after lung resection injury. Here, a 3D biomimetic porous collagen scaffold with similar structure characteristics as lung is fabricated, and a novel collagen binding hepatocyte growth factor (CBD-HGF) is tethered on the collagen scaffold for maintaining the biomimetic function of HGF to improve the lung regeneration microenvironment. The biomimetic scaffold was implanted into the operative region of a rat partial lung resection model. The results revealed that vascular endothelial cells and endogenous alveolar stem cells entered the scaffold at the early stage of regeneration. At the later stage, inflammation and fibrosis were attenuated, the microvascular and functional alveolar-like structures were formed, and the general morphology of the injured lung was restored. Taken together, the functional 3D biomimetic collagen scaffold facilitates recovery of the injured lung, alveolar regeneration, and angiogenesis after acute lung injury. Particularly, this is the first study of lung regeneration in vivo guided by biomimetic collagen scaffold materials, which supports the concept that tissue engineering is an effective strategy for alveolar regeneration.